Legal pluralism a study on the application of Taritib, Islamic and secular laws on land ownership among the Maranaos - Borowa, Shalma 1975- (2005)
This study entitled " Legal pluralism :a study on the applications of Taritib, Islamic and secular laws on land ownership among the Maranaos" examines how the Maranao society addresses soem problems on legal pluralism as a result of the operation of three (3) laws, namely : Taritib, Islamic and secular laws. However, thsi study focuses only on the application of Taritib, Islamic and secular laws on land ownership. Today, one of the most talked about problems on land ownership considering the operations of the three (3) laws. Thus, this study addresses the following questions : (1) What is legal pluralism and how is it shown in the Maranao society? (2) How has legal pluralism worked in the settlement of land ownership cases among Maranaos? (3) What are the effects of the operation of Taritib and secular laws on the Maranao society?